La producción y la comprensión de la ciencia : la elaboración en el aprendizaje de la ciencia escolar - Otero, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper criticizes the conceptual reformulations of science made with pedagogical purposes and, more particularly, the absence of reference to originary problems.